UJI VALIDITAS DAN RELIABILITAS DALAM PENELITIAN EPIDEMIOLOGI KEDOKTERAN GIGI - Ristya Widi E (Fakultas Kedokteran Gigi Universitas Jember, 2011)
In epidemiology research, equipment for collecting the data majority used questionnaire. Questionnaire which is used must be valid and reliable for answering the health problems, so that prior to do the research, one first step must be done is testing the questionnaire validity and reliability. Validity is an index which shows that the measurement equipment measures the data correctly. Validity test may use product moment correlation technique for each score questionnaire’s numbers with total score (total of score questionnaire). Instrument is valid if correlation value (pearson correlation) is positive, and probability value [sig. (2-tailed)] is less than significant value (α 0,05). Reliability is index which show that equipment research can be to beleaved and trade on. Reliability test may use Cronbach’s Alpha method. The questionnaire is reliable if Cronbach’s Alpha value is more than r table value.